Stability evaluation of deep-buried TBM construction tunnel based on microseismic monitoring technology. (November 2018) - Tang, Zhili; Liu, Xiaoli; Xu, Qianjun; Li, Chaoyi; Qin, Pengxiang
Highlights: The characteristics of microseismic (MS) events are consistent with TBM activity. The precursor of instability is a concentration of MS events in space and time. An inverse relation between the b-values of MS events and depth can be observed. The inverted velocity field reflects the influence of excavation disturbances. Abstract: During the construction of Duoxiongla tunnel in Tibet, China, instabilities of the surrounding rock such as rock spalling, rock collapses and rockbursts frequently occurred. An advanced microseismic (MS) monitoring system was built to monitor and evaluate the stability of the rock masses under tunnel boring machine (TBM) excavation. The monitoring results reveal the tempo-spatial distribution of the MS events in unstable areas and enable the relationship between the number and energy of MS events and TBM activity to be established. Furthermore, nonroutine methods such as magnitude–frequency analysis and double-difference tomography are used to assess the stability of the tunnel. These results show that: (1) The precursor of instability of surrounding rock is a concentration of MS events in space and time; (2) The temporal distribution of b-values is consistent with the actual situation of the tunnel, and an inverse relation between the b-values and depth can be observed. The smaller the b-value, the greater the risk of instability of the surrounding rock; (3) The distribution of the velocity field inverted by double-difference tomography can effectively reflect the influence of excavation disturbances. Based on the results of MS monitoring and analysis of Duoxiongla Tunnel, an integrated approach is proposed, which is promising for assessing the stability of similar deep-buried TBM construction tunnels.